2017
DOI: 10.1002/pola.28890
|View full text |Cite
|
Sign up to set email alerts
|

Visible light‐induced RAFT polymerization of methacrylates with benzaldehyde derivatives as organophotoredox catalysts

Abstract: The benzaldehyde derivatives, such as 2,4‐dimethoxy benzaldehyde (PC1) and p‐anisaldehyde (PC2), were successfully used as photoredox catalysts (PCs) in combination with typical RAFT agent 4‐cyano‐4‐(phenylcarbonothioylthio)pentanoic acid (CTP) for the controlled photoinduced electron transfer RAFT polymerization (PET‐RAFT) of methyl methacrylate (MMA) and benzyl methacrylate (BnMA) at room temperature. The kinetics of the polymerizations showed first order with respect to monomer conversions. Besides, the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…The reduction potential (E θ cat ⋅+ /cat*) of p ‐methoxybenzaldehyde (PMOB), PCB, and DPAB is −2.19 V, −2.42 V, and −1.61 V, respectively. [ 40–44 ] For the RAFT polymerization, a highly reductive photocatalyst exhibited a better catalytic effect. [ 51 ] In addition, the reaction between dithiol and divinyl has been carried out using triethylamine as a catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction potential (E θ cat ⋅+ /cat*) of p ‐methoxybenzaldehyde (PMOB), PCB, and DPAB is −2.19 V, −2.42 V, and −1.61 V, respectively. [ 40–44 ] For the RAFT polymerization, a highly reductive photocatalyst exhibited a better catalytic effect. [ 51 ] In addition, the reaction between dithiol and divinyl has been carried out using triethylamine as a catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…[ 38–42 ] In recent studies, a series of benzaldehyde derivatives such as p ‐cyanobenzaldehyde (PCB) were used in controlled living radical polymerization. [ 43–45 ] In the study of Zhang et al, [ 46 ] 4‐( N,N ‐diphenylamino)‐benzaldehyde (DPAB) was applied as a photocatalyst to the RAFT system and had a positive effect on the rate and controllability of the reaction. However, it has not been reported that a benzaldehyde derivative is used as a catalyst for thiol–ene radical reaction yet.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the effect of different photoredox catalyst on the PET‐RAFT polymerization of p ‐MS at room temperature, we kept the optimized polymerization conditions constant and changed the type of photoredox catalyst (PC1, PC2, and PC3). According to the mechanism of PET‐RAFT polymerization, the reduction potential of PCs (PC1, −2.19 V vs. SCE; PC2, −2.60 V vs. SCE; PC3, −2.42 V vs. SCE) were much lower than the reduction potential of RAFT agent, PC* was able to reduce RAFT agent through a photoinduced electron transfer process and then produced a radical (Pn•). Generally, the more negative redox potential value that PCs have, the greater reactivity in the activation of RAFT agent.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve this catalytic system, we proposed a new controlled radical polymerization method. By using aromatic aldehydes that mentioned above as photoredox catalysts in combination with 4‐cyano‐4‐(phenylcarbonothioylthio)‐pentanoic acid (CTP) for the controlled PET‐RAFT of methyl methacrylate (MMA) and benzyl methacrylate (BnMA) at room temperature, the living features of polymerizations have also been further supported by chain extension and synthesis of PMMA‐ b ‐PBnMA diblock copolymer …”
Section: Introductionmentioning
confidence: 99%
“…So far, the main living radical polymerizations ATRP and RAFT could both be initiated by the PET method . However, many researchers have used metal complexes as photocatalysts, which offer clear advantages in that the changes in the oxidation state are fixed and they can be efficiently changed, so that a low catalyst concentration can be employed .…”
Section: Introductionmentioning
confidence: 99%